Specyfika hydrochemiczna wód jeziora Modła wynikająca z uwarunkowań geograficznych - Cieśliński, Roman; Olszewska, Alicja (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2009)
There is a lot of articles about coastal lakes where Modła Lake is unfortunately pass over. Modła Lake is situated on Polish coast of South Baltic. The results of research indicated that Modła Lake should be classified to coastal lakes because of being similar to typical coastal lakes in spite of some attributes differentiating it from that group. Occurrent periodically the increasing salination of waters in Modła Lake and moreover batymetry of describing Lake, is main attribute that testifying about its coastal character quality.